PENGARUH INVESTASI, DANA PERIMBANGAN DAN PAD TERHADAP KEMISKINAN DAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Diastari Putri, Ni Putu Asri; Sri Budhi, Made Kembar; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Being one of the popular tourist destinations for tourists encourages the Province of Bali to always strive for the public welfare. The public welfare of a region’s people can be seen from the Human Development Index (HDI). The research objective to be analyze the effect of investment, balance fund, original regional income on poverty; analyze the influence of investment, balance fund, original regional income, and poverty on the welfare; and analyze the influence of investment, balance fund, original regional income through poverty on the welfare in the Regency/City in the Province of Bali. This study uses secondary data in the Regency / City Province of Bali in the period 2011-2017 with path analysis techniques. The results of analysis showed that, 1) investment has a negative and not significant effect on poverty, while the balance fund and PAD have a significant effect on poverty, 2) investment, the balance fund has a significant positive effect and poverty has a significant negative effect on community welfare, whereas PAD has no significant positive effect on community welfare, 3) income Native regions affect the welfare of the community through poverty, while investment and balance funds do not affect the welfare of the community through poverty. Keywords : Investation, balance fund, original regional income, poverty, public welfare.